Understanding Dietary Intervention-Mediated Epigenetic Modifications in Metabolic Diseases - Asif, Shaza; Morrow, Nadya M.; Mulvihill, Erin E.; Kim, Kyoung-Han (Frontiers in Genetics, 2020)
The global prevalence of metabolic disorders, such as obesity, diabetes and fatty liver disease, is dramatically increasing. Both genetic and environmental factors are well-known contributors to the development of these diseases and therefore, the study of epigenetics can provide additional mechanistic insight. Dietary interventions, including caloric restriction, intermittent fasting or time-restricted feeding, have shown promising improvements in patients’ overall metabolic profiles (i.e. reduced body weight, improved glucose homeostasis), and an increasing number of studies have associated these beneficial effects with epigenetic alterations. In this article, we review epigenetic changes involved in both metabolic diseases and dietary interventions in primary metabolic tissues (i.e. adipose, liver, pancreas) in hopes of elucidating potential biomarkers and therapeutic targets for disease prevention and treatment.